Host-parasite interactions and mechanisms of infection in amebiasis - Suriptiastuti, Suriptiastuti (Faculty of Medicine, Trisakti University, 2010)
Amebiasis is caused by E. histolytica, which is the only species pathogenic in humans, while the pathogeneicity of E. dispar and E. moshkovskii is still unclear. The disease is endemic in the developing countries, mainly due to poor sanitation and lack of clean water supplies. Infection occurs by ingestion of E. histolytica cysts in fecally contaminated food or water. Excystation in the small intestine releases motile invasive trophozoites which migrate to the large intestine, adhere to the colonic epithelium by means of galactose and an amebic surface antigen, N-acetyl-D-galactosamine-specific lectin. This results in killing of epithelial cells, neutrophils, and lymphocytes by the trophozoites, presumably through secretion of the pore-forming proteins called amebapores and activation of caspase 3. The trophozoite virulence factor, cysteine proteinase, induces an inflammatory response, resulting in neutrophil-mediated damage. Hematogenous spread of trophozoites causes extraintestinal amebiasis, particularly amebic liver abscess (ALA), in the formation of which caspase 3 presumably also plays a role. The trophozoites in the liver induce tissue destruction, cellular necrosis and formation of microabcesses that coalesce into a large solitary abscess in 65-75% of cases. Results from pediatric studies reveal that partial immunity is acquired after infection with E.histolytica, the immunity however declining with age.